Identification of Metastasis-Associated MicroRNAs in Metastatic Melanoma by miRNA Expression Profile and Experimental Validation - Gao, Yunshu; Xu, Jiahua; Li, Hongwei; Hu, Yi; Yu, Guanzhen (Frontiers in Genetics, 2021)
It is reported that microRNAs (miRNA) have paramount functions in many cellular biological processes, development, metabolism, differentiation, survival, proliferation, apoptosis included, some of which are involved in metastasis of tumors, such as melanoma. Here, 3 metastasis-associated miRNAs, miR-18a-5p (upregulated), miR-155-5p (downregulated) and miR-93-5p (upregulated), were identified from a total of 63 different expression miRNAs (DEMs) in metastatic melanoma compared with primary melanoma. We predicted 262 target genes of miR-18a-5p, 904 miR-155-5p target genes and 1220 miR-93-5p target genes. They participated in pathways concerning melanoma, such as TNF signaling pathway, pathways in cancer, FoxO signaling pathway, cell cycle, Hippo signaling pathway, TGF-beta signaling pathway. We identified the top 10 hub nodes whose degrees were higher for each survival-associated miRNA as hub genes through constructing the PPI network. Using the selected miRNA and the hub genes, we constructed the miRNA-hub gene network, and PTEN and CCND1 were found to be regulated by all the three miRNAs. Of note, miR-155-5p was obviously downregulated in metastatic melanoma tissues, miR-18a-5p and miR-93-5p were obviously regulated positively in metastatic melanoma tissues. In validating experiments, miR-155-5p’s overexpression or inhibited miR-18a-5p’s and miR-93-5p’s expression could all significantly reduce SK-MEL-28 cells’ invasive ability. Finally, miR-93-5p and its potential target gene UBC were selected for further validation. We found that miR-93-5p’s inhibition could reduce SK-MEL-28 cell's invasive ability through upregulated the expression of UBC, and the anti-invasive effect was reserved by downregulation of UBC. The results show that the selected 3 metastasis-associated miRNAs participate in the process of melanoma metastasis via regulating their target genes, providing a potential molecular mechanism for this disease.